Unremarkably Gay: Post-Gay Life in Sydney: Несензационалистички геј: Постгеј животот во Сиднеј - Rеynolds Robert; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Robert Rеynolds | Роберт Рејнолдс Title (English): Unremarkably Gay: Post-Gay Life in Sydney Title (Macedonian): Несензационалистички геј: Постгеј животот во Сиднеј Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 201-234 Page Count: 34 Citation (English): Robert Rеynolds, “Unremarkably Gay: Post-Gay Life in Sydney,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 201-234. Citation (Macedonian): Роберт Рејнолдс, „Несензационалистички геј: Постгеј животот во Сиднеј“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 201-234.